DAMPAK EKONOMI PENGEMBANGAN COMMUNITY BASED TOURISM TERHADAP MASYARAKAT LOKAL DI KABUPATEN MALANG (Studi Kasus Destinasi Wisata Cafe Sawah Pujon Kidul) - Agfianto, Tomi; Antara, Made; Suardana, I Wayan (Jurnal Master Pariwisata (JUMPA); Volume 05, Nomor 02, Januari 2019, 2019)
This study aims to identify and analyze the extent to which CBT can have an impact on the income of local people originating from tourist expenditure in tourist destinations. This study uses quantitative research methods from the results of questionnaires to tourists, labor, business units, and managers at Cafe Sawah tourist destinations in Pujon Kidul Village, Malang Regency. The finding in this study is that the multiplier effect value in the Cafe Sawah tourist destination has a Keynesian Income Multiplier number of 0.27 or 00 1.00, so that the destination has not been able to have a significant impact on the surrounding community, especially those who do business in that location. The results of this study explain that Community Based Management has not been able to provide a significant impact, so there needs to be a fundamental evaluation of the local district government where the function of the government is as a regulation and providing assistance to existing tourism destinations in the area.   Keywords : Community Based Tourism, Sustainable Tourism, Tourism Economic Impact, Cafe Sawah